Potensi Brownies Ubi Jalar Ungu terhadap Status Gizi Kurang pada Balita Tahun 2022 - Latifah, Nafi'atul; Pujiastuti, Rr. Sri Endang; Sudirman, Sudirman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the effect of purple sweet potato brownies on improving nutritional status in malnourished toddlers in the working area of ​​Ponggok Health Center, Ponggok District, Blitar Regency. The research method used is proper experimental using a pre-test and post-test control group design. The study results showed that the average increase in nutritional status in the intervention group improved the nutritional status of toddlers in body weight (p-value = 0.000). The average increase in nutritional status improved the nutritional status of toddlers with height (p-value = 0.000). The average increase in nutritional status improved the nutritional status of LILA toddlers (p-value = 0.000). The conclusion is that giving purple sweet potato brownies can improve the nutritional status of toddlers. From the study results, giving purple sweet potato brownies tends to improve the nutritional status of toddlers more than just using green bean porridge. Keywords: Undernourished Toddlers, Purple Sweet Potato Brownies, Nutritional Status